Connect, communicate, collaborate and create: Implementing an enterprise-wide social collaboration platform at KPMG – Part two: Realizing value. (December 2013) - Hughes, Ceri; Chapel, Alex
As discussed in the authors' previous article, KPMG has introduced an internal social collaboration platform called the Hub across its international network. The Hub has now been adopted by a large number of users across multiple member firms. It aims to help KPMG professionals connect, communicate, collaborate and create more effectively together. Business benefits observed include reduced time taken to collaborate on ideas, initiatives, proposals and increased speed in responding to client and market opportunities; improved access to expertise and experience around the KPMG international network, increased engagement and the ability to deliver targeted, contextual communications. The Hub also allows client service teams to benefit from these improved ways of working in highly secure, private subject areas so that client matters can be openly discussed but are accessible and visible only to those who should legitimately have access. This new way of working together requires awareness of the professional obligations of each KPMG professional in regard to data privacy and client confidentiality. This is addressed by the change management programme accompanying the Hub, which includes each user's acceptance of the Rules of the Road, a set of behavioural guidelines to help users understand the conduct expected, which is also monitored by the central Hub team. The change management programme underpinning the implementation of the Hub is centred on the belief that a new set of organizational capabilities, rather than a toolset or technology platform, is being delivered. Helping Hub users understand the behaviours that the Hub is expected to help cultivate is an important part of that change management programme. This will remain an important tenet of the ongoing, multi-year journey of both the Hub implementation and the realization of the benefits to be delivered.